Pemberdayaan Masyarakat Melalui Bimbingan Belajar dalam Meningkatkan Kemampuan Akademik Pada Peserta Didik Sekolah Dasar Negeri di Wilayah UPT. Pulau Malan SP.1A Desa Buntut Bali, Kecamatan Pulau Malan Kabupaten Katingan - Danella Merdiasi; Rusiana Rusiana; Thiyo Eko Julyanto; Melika Melika; Natalia Marleti; Nova Kurniati; Rebecka Gloria; Renol Van Hofe; Siska Ariani; Tia Natalia; Vera Vera; Yemila Yemila (Universitas Pahlawan Tuanku Tambusai, 2022)
The Real Work Lecture Program (KKN) held is tutoring activities. This tutoring activity is expected to improve students' skills, especially in the ability to read, write, count and basic English so that it affects student learning outcomes. This tutoring program focuses on students who are lacking in academic abilities, the limited support activities provided such as the absence of tutoring in the village and the lack of educators in schools. This tutoring is carried out outside of school hours and is carried out three times a week, namely Monday, Tuesday and Saturday. The method used is the Participatory Action Research method consisting of knowing (knowing the problem with observations and interviews), understanding (understanding the problems that exist in school), planning (making activity plans), acting (implementing tutoring activities) and reflecting (reflecting). This activity is the interest and results of reading, writing, arithmetic and understanding related to the basics of english.